E-Referral System Modeling Using Fuzzy Multiple-Criteria Decision Making - Gandung Triyono; Sri Hartati; Reza Pulungan; Lutfan Lazuardi (Institute of Advanced Engineering and Science, 2018)
Currently, the quality of health services in Indonesia is getting better. However, the referral system still has some problems. The first is the difficulty in determining the referral hospital by the condition of the patient. The second is the different parameters used to determine the referral hospitals between countries. Based on those problems, it is necessary to improve the ability of the current referral system. This study developed a reference system model for assessing the suitability of the patient's background with the referral hospital. Some of the methods used are restful on web service technologies for information exchange between primary health care doctors and referral hospitals, Fuzzy Multiple-Criteria Decision Making (FMCDM) to determine the ranking of referral hospitals that fit the patient's background. The result of this study is an intelligent system model to get the referral hospital that fit the patient's background.